A negative electrode sheet, a method for manufacturing the same, and an application thereof
Patent Information
- Application Number
- CN202611029649.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-10
- Publication Date
- 2026-10-09
AI Technical Summary
[0006]本发明提供了一种负极极片及其制备方法和应用,以解决相关技术中石墨/硅碳复合负极极片因硅材料在充放电过程中发生巨大体积膨胀(通常超过300%)所导致的电极颗粒粉化、导电网络断裂、活性物质与集流体剥离、SEI膜反复破裂与修复、循环寿命急剧衰减的问题;同时克服现有技术中多层涂布工艺存在的层间界面阻抗高、易分层、工艺复杂、成本高昂的缺陷,以及均匀造孔技术无法实现梯度应力缓冲、难以兼顾高压实密度与膨胀缓冲能力的局限性
(1)通过构建由内向外孔隙率递增的梯度结构,外层高孔隙率区域(35%-50%)为硅材料的体积膨胀提供了充足的缓冲空间,可容纳硅颗粒的体积变化,避免电极整体膨胀、粉化和脱落;内层低孔隙率区域(15%-25%)保证了活性物质与集流体的紧密结合以及良好的电子导电网络。经测试,采用本发明极片的电池循环500周后,极片厚度膨胀率低于25%,容量保持率高达85%以上,性能明显优于传统均匀造孔或多层涂布极片。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium-ion battery technology, specifically to a negative electrode sheet, its preparation method, and its application. Background Technology
[0002] With the increasing demands for energy density in new energy vehicles and consumer electronics, lithium-ion battery anode materials are evolving from single graphite to silicon-carbon composite materials. Compared to traditional graphite anodes (372 mAh / g), silicon-carbon anodes have a higher theoretical specific capacity (≥1500 mAh / g), but they experience volume expansion of over 300% during charge and discharge. This drastic volume effect easily leads to electrode particle pulverization, conductive network breakage, repeated SEI film rupture, and peeling of active material from current collector, severely limiting the battery's cycle life. To address this, the industry has proposed various improvement schemes, including nano-sizing, carbon coating, binder modification, and electrode structure design.
[0003] In electrode structure design, existing technologies mainly construct gradient pore structures through multilayer coating processes. This method involves coating slurries with different pore-forming agent contents layer by layer to form a structure where porosity increases from the inside out. However, multilayer coating processes are cumbersome, requiring multiple batching, coating, and drying steps, resulting in high production costs and low efficiency. Moreover, the physical interfaces between layers have weak bonding under silicon volume expansion stress, making them prone to delamination and increasing interfacial impedance, thus deteriorating the rate performance of the battery.
[0004] Another existing technology employs a single-layer coating process with uniform addition of a pore-forming agent to form a uniform porous structure. Although this process is simple, the uniform pores cannot meet the functional requirements of electrodes at different depths and are difficult to effectively buffer volume expansion.
[0005] Therefore, developing a negative electrode that is simple to manufacture, low in cost, and can balance interfacial bonding strength, expansion buffering capacity, and energy density has become an urgent technical problem to be solved in this field. Summary of the Invention
[0006] This invention provides a negative electrode sheet, its preparation method, and its application, to solve the problems of electrode particle pulverization, conductive network breakage, active material and current collector peeling, repeated SEI film rupture and repair, and sharp decline in cycle life caused by the huge volume expansion (usually exceeding 300%) of silicon material during charging and discharging in graphite / silicon-carbon composite negative electrode sheets in related technologies. At the same time, it overcomes the defects of high interlayer interface impedance, easy delamination, complex process, and high cost of multilayer coating process in the prior art, as well as the limitations of uniform pore formation technology in achieving gradient stress buffering and difficulty in balancing high solid density and expansion buffering capacity.
[0007] To achieve the above objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a negative electrode sheet, comprising: current collector; An active material layer is disposed on at least a portion of the surface of the current collector; wherein the active material layer is a single-layer structure, and the porosity of the active material layer increases in a gradient from the side closer to the current collector to the side farther away from the current collector, with the porosity on the side closer to the current collector being 15%-25% and the porosity on the side farther away from the current collector being 35%-50%.
[0008] In some embodiments, the active material layer includes graphite, silicon-carbon composite material, conductive agent, and binder.
[0009] Secondly, the present invention provides a method for preparing the aforementioned negative electrode sheet, comprising: Prepare a slurry containing graphite, silicon carbide composite material, binder, solvent and pore-forming agent; The slurry is coated onto at least a portion of the surface of the current collector to form a wet film; The wet film is subjected to segmented drying. The dried electrode sheet is heat-treated to obtain the negative electrode sheet.
[0010] In some embodiments, the pore-forming agent accounts for 3%-15% of the mass of the slurry.
[0011] In some embodiments, the average particle size of the pore-forming agent is 50 nm to 1 μm.
[0012] In some embodiments, the pore-forming agent includes at least one selected from polymethyl methacrylate microspheres, ammonium bicarbonate, polystyrene microspheres, polylactic acid microspheres, ammonium carbonate, and ammonium oxalate.
[0013] In some embodiments, the segmented drying process includes a first stage drying process and a second stage drying process, wherein the temperature of the first stage drying process is lower than the temperature of the second stage drying process, and the wind speed of the first stage drying process is lower than the wind speed of the second stage drying process.
[0014] In some embodiments, the temperature of the first drying process is 40°C-60°C, and the drying time is 5 min-20 min.
[0015] In some embodiments, the temperature of the second drying process is 80°C-120°C, and the drying time is 10 min-30 min.
[0016] In some embodiments, the heat treatment is performed at a temperature of 150°C to 300°C for a duration of 1 hour to 6 hours.
[0017] Thirdly, the present invention provides a lithium-ion battery comprising the aforementioned negative electrode sheet.
[0018] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) By constructing a gradient structure with increasing porosity from the inside out, the outer high-porosity region (35%-50%) provides sufficient buffer space for the volume expansion of silicon material, which can accommodate the volume change of silicon particles and avoid overall electrode expansion, pulverization and shedding; the inner low-porosity region (15%-25%) ensures the tight bonding between the active material and the current collector and a good electronic conductivity network. After testing, the battery using the electrode of this invention has a thickness expansion rate of less than 25% and a capacity retention rate of more than 85% after 500 cycles, which is significantly better than the traditional uniformly formed or multi-layer coated electrode.
[0019] (2) This invention employs a single-layer coating process, achieving a concentration gradient of the pore-forming agent through physical migration during the drying process, ultimately forming a pore gradient structure and eliminating the interlayer interface caused by multi-layer coating. This structure eliminates the risk of interlayer delamination and significantly reduces interface impedance, which is beneficial for improving the rate performance and cycle life of the battery.
[0020] (3) The preparation process provided in this application is simple, cost-controllable, and easy to industrialize. No modification to existing coating equipment is required; only optimization of the drying temperature curve (two-stage drying) and addition of a pore-forming agent on the basis of conventional single-layer coating are needed to achieve the construction of gradient structures. The process flow is short, the production efficiency is high, the production cost is low, and it is suitable for large-scale production.
[0021] (4) In the negative electrode provided in this application, the high porosity of the surface layer is conducive to the rapid penetration of electrolyte into the electrode, shortening the standing time after liquid injection by more than 30%, and at the same time, it is conducive to the rapid transport of lithium ions inside the electrode, improving the rate performance of the battery.
[0022] (5) While ensuring a high compaction density (≥1.55 g / cm³), it can still provide sufficient buffer space and structural stability, thereby achieving a synergistic improvement in energy density and cycle life. Detailed Implementation
[0023] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Obviously, the described embodiments are only some, not all, of the embodiments of this invention. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0024] As the demands for extended battery life from new energy vehicles and consumer electronics continue to rise, lithium-ion battery anode materials are upgrading from single graphite to silicon-carbon composite materials. The theoretical specific capacity of silicon-carbon anodes (≥1500 mAh / g) is significantly higher than that of traditional graphite anodes (372 mAh / g), but the volume expansion rate of silicon particles during charge and discharge is over 300%. This massive volume change leads to electrode structure damage, repeated rupture and repair of the SEI film, and delamination of the active material from the current collector, resulting in a sharp decline in cycle life. To address this issue, the industry has developed various technical approaches, including silicon particle nanosizing, carbon coating, binder modification, and electrode structure design.
[0025] In electrode structure design, existing technologies typically employ multilayer coating processes to fabricate electrodes with gradient porosity. This method involves preparing multiple slurries with varying pore-forming agent contents, coating them layer by layer onto the current collector surface in ascending order of pore-forming agent content. After drying, rolling, and heat treatment, a gradient structure with increasing porosity from the inside out is formed along the thickness direction. While this method allows for precise control of the porosity gradient, it still has significant limitations: First, multilayer coating requires separate preparation, coating, and drying of each slurry layer, resulting in a lengthy process, extremely high equipment precision requirements, and a significant increase in production costs. Second, physical interfaces inevitably exist between adjacent coatings. Under the repeated stress generated by silicon expansion, the interlayer bonding is weak, making delamination and peeling prone to occur, leading to electrode structure failure. Furthermore, interlayer interfaces increase electron and ion transport impedance, reducing the battery's rate performance and energy efficiency.
[0026] Another existing technology involves uniformly adding a pore-forming agent to the slurry, followed by conventional single-layer coating, drying, and heat treatment to form a uniformly distributed pore structure within the electrode coating. This method aims to provide buffer space for silicon expansion and improve electrolyte wettability by increasing the overall porosity. However, a uniform pore structure cannot achieve differentiated functional matching: the inner layer near the current collector also has high porosity, which reduces the bonding strength between the active material and the current collector, as well as the continuity of the electronic conductive network, leading to decreased electrode peel strength and deterioration of rate performance. Simultaneously, uniform pores cannot guide the stress gradient distribution, and the stress generated by silicon expansion easily forms localized concentration points within the electrode, accelerating electrode pulverization. Furthermore, to provide sufficient buffer space, a large amount of pore-forming agent is often required, which significantly reduces the electrode compaction density, thus sacrificing the battery's volumetric energy density.
[0027] In view of this, the present invention provides a negative electrode sheet, its preparation method, and its application, aiming to solve the problems of electrode pulverization, conductive network breakage, and cycle life degradation caused by the huge volume expansion of silicon materials in graphite / silicon-carbon composite negative electrode sheets. Simultaneously, the present invention can overcome the shortcomings of existing multilayer coating processes, such as high interlayer interface impedance, easy delamination, complex processes, and high costs, as well as the limitations of uniform pore-forming technology in achieving gradient stress buffering and balancing high solid density and expansion buffering capacity. Thus, it achieves low-cost and high-efficiency preparation of high-performance silicon-carbon negative electrode sheets.
[0028] In a first aspect, the present invention provides a negative electrode sheet. According to an embodiment of the present application, the negative electrode sheet includes a current collector and an active material layer disposed on at least a portion of the surface of the current collector, wherein the active material layer is a single-layer structure, and along the thickness direction of the active material layer, the porosity within the active material layer increases in a gradient from the side closer to the current collector to the side farther away from the current collector.
[0029] The negative electrode sheet provided by this invention achieves a differentiated distribution of internal functions by constructing a pore gradient structure with gradually increasing porosity from the inside to the outside within a single layer of active material. The low-porosity region near the current collector ensures a tight bond between the active material and the current collector, as well as the continuity of the electronic conductivity network. The high-porosity region further away from the current collector provides ample buffer space for the volume expansion of the negative electrode material, effectively preventing electrode pulverization and detachment. This structure effectively improves structural stability while maintaining high compaction density, resulting in a capacity retention rate of over 85% and an electrode thickness expansion rate of less than 25% after 500 battery cycles. Furthermore, the high surface porosity facilitates rapid electrolyte penetration and lithium-ion transport, shortens the electrolyte filling and settling time, and improves rate performance, thereby achieving a synergistic improvement in energy density and cycle life.
[0030] Furthermore, the porosity on the side closer to the current collector is 15%-25%, and the porosity on the side farther from the current collector is 35%-50%.
[0031] By limiting the porosity to 15%-25% on the side closer to the current collector and 35%-50% on the side farther from the current collector, and forming a 25%-35% porosity gradient transition in the middle region, this invention constructs a continuous gradient structure with increasing porosity from the inside to the outside within the active material layer. The inner low-porosity region ensures the interfacial bonding strength between the active material and the current collector, as well as the integrity of the electronic conductivity network, avoiding increased interfacial impedance and electrode peeling risks caused by excessive porosity. The outer high-porosity region provides ample buffer space for the volume expansion of the negative electrode material, effectively alleviating stress concentration and inhibiting particle pulverization and active material shedding.
[0032] This application does not impose any particular limitation on the material of the current collector, and those skilled in the art can select it according to actual needs. Exemplarily, the current collector may be selected from at least one of copper foil, carbon-coated copper foil, or nickel-plated copper foil. In some embodiments, the current collector is copper foil.
[0033] It should be noted that the active material layer mainly consists of a negative electrode active material, a conductive agent, and a binder, wherein the negative electrode active material includes graphite and silicon-carbon composite materials. The conductive agent includes, but is not limited to, single-walled carbon nanotubes, multi-walled carbon nanotubes, and conductive carbon black. The binder includes, but is not limited to, polyacrylic acid, polyurethane, and styrene-butadiene rubber.
[0034] Secondly, the present invention provides a method for preparing the aforementioned negative electrode sheet. According to an embodiment of this application, the preparation method includes the following steps: S100: Prepare negative electrode slurry.
[0035] Graphite, silicon-carbon composite material, conductive agent, binder and pore-forming agent are mixed and added to solvent and stirred evenly to obtain negative electrode slurry.
[0036] In some embodiments of the present invention, the pore-forming agent accounts for 3%-15% of the mass of the slurry. Limiting the mass percentage of the pore-forming agent within this range serves several purposes: First, when the percentage is ≥3%, the additional pore volume generated after the decomposition of the pore-forming agent is sufficient to form a detectable and reproducible pore gradient (porosity difference between inner and outer layers ≥10 percentage points), providing a differentiated buffer for silicon expansion; if it is below this value, the pore gradient is weak and cannot function effectively. Second, when the percentage is ≤15%, the binder network in the electrode remains continuous, with a peel strength ≥15 N / m, meeting processing requirements; if this upper limit is exceeded, excessive pores will rupture the binder network, leading to electrode embrittlement, cracking, and powder shedding. Third, within the 3%-15% range, the particle spacing of the pore-forming agent is moderate, ensuring smooth and efficient migration during segmented drying capillary flow without unstable migration paths due to excessively low concentrations or particle blockage and self-limiting effects due to excessively high concentrations. Fourth, this range achieves an optimized balance between energy density loss (≤8%) and improved cycle life (capacity retention increased from 78.6% to 91.2%). Fifth, the gas released by the decomposition of the pore-forming agent can escape in a stepped manner through the pre-formed through-channels on the surface, avoiding blistering or cracking of the coating due to a sudden increase in internal pressure. In summary, the 3%-15% proportion range ensures the effective construction of the pore gradient, the synergistic achievement of electrode mechanical integrity and process stability.
[0037] In some embodiments of the present invention, the average particle size of the pore-forming agent is 50 nm-1 μm. Limiting the average particle size of the pore-forming agent to this range has two advantages: First, this particle size range matches the equivalent pore size of the capillary channels in the coating (approximately 50 nm-500 nm). The pore-forming agent microspheres can be effectively carried to the surface by the capillary flow generated by solvent evaporation, without being mechanically locked by the graphite skeleton, ensuring migration efficiency and directional consistency. If the particle size exceeds 1 μm, the migration resistance increases sharply or even blocks the channels, reducing the migration efficiency by more than 60%. If it is below 50 nm, Brownian motion dominates, the directional migration ability is lost, and a clear gradient cannot be formed. Second, this particle size, after decomposition, forms submicron-level pores (approximately 40 nm-1.2 μm), which is sufficient to ensure sufficient electrolyte wetting and rapid lithium ion transport. Simultaneously, the pore wall thickness is moderate, making it less prone to crushing or blockage during rolling and cycling, maintaining structural stability. Third, the particle size is much smaller than graphite (5-20 μm) and close to that of the conductive agent. In the wet film, it preferentially migrates with the solvent, while the conductive agent, due to its chain-like aggregate structure, is locked in the network. This achieves "selective migration" of the pore-forming agent while the conductive agent remains largely immobile, ensuring the uniformity of the conductive network. Fourth, the 1 μm particle size limit ensures that the pore-forming agent is easily dispersed and does not easily settle during slurry preparation and coating, which is beneficial to slurry stability and coating consistency. In summary, the particle size range of 50 nm to 1 μm ensures the synergistic achievement of migration effect, pore function, system compatibility, and process stability.
[0038] In some embodiments of the present invention, the pore-forming agent is a substance that can completely decompose within the range of 150-300 °C. Limiting the decomposition temperature of the pore-forming agent to this range has two advantages: First, this temperature window is much lower than the significant oxidation temperature of copper foil current collectors (above approximately 350 °C) and the oxidation initiation temperature of graphite, ensuring that the current collector does not oxidize or change color during heat treatment, the contact resistance does not increase, and the crystal structure of the active material is not damaged by heat. Second, this window is higher than the conventional drying temperature (80-120 °C), allowing the pore-forming agent to remain solid and complete migration during the low-temperature, low-speed segment of segmented drying, until decomposition is triggered by a subsequent independent heat treatment process. This achieves the decoupling of the two functions of "migration" and "pore formation" in time and space, which is the premise for the realization of the "first forming a concentration gradient, then converting it into a pore gradient" technical path of this patent. If the decomposition temperature is below 150℃, the pore-forming agent will prematurely vaporize and escape during the first stage of drying, failing to migrate to the surface and resulting in gradient construction failure. If the temperature is above 300℃, a higher heat treatment temperature is required, which will lead to irreversible decomposition of the binder, breakage of the electrode bonding network, a sharp drop in peel strength to below 10N / m, and a significant increase in the risk of copper foil oxidation. Thirdly, the heating conditions of 150-300℃ are easily achieved in industrial ovens or tunnel furnaces with high temperature control precision. Pore formation can be completed without inert gas protection, offering a wide process window, simple operation, and low equipment cost, making it suitable for large-scale continuous production. Fourthly, the decomposition products of the pore-forming agent at this decomposition temperature (such as PMMA decomposing at approximately 240-400℃ and ammonium bicarbonate decomposing at 36-100℃, with actual heat treatment completed within 150-300℃) are all gaseous small molecules with no solid residue, preventing the introduction of impurities or side reactions and ensuring the purity of the electrode interface. In summary, the decomposition temperature range of 150-300℃ ensures functional decoupling of the pore-forming agent in the process sequence, thermal safety of the various components of the electrode during heat treatment, industrial feasibility, and cleanliness of the decomposition products.
[0039] For example, the pore-forming agent includes, but is not limited to, polymethyl methacrylate (PMMA) microspheres, ammonium bicarbonate, polystyrene microspheres, polylactic acid microspheres, ammonium carbonate, ammonium oxalate, etc.
[0040] It should be noted that different pore-forming agents have different thermal decomposition temperatures. In the actual preparation process, the temperature and time parameters of the heat treatment can be adjusted according to the specific decomposition characteristics of the selected pore-forming agent to ensure that the pore-forming agent is fully decomposed and removed, while avoiding thermal damage to the negative electrode active material.
[0041] S200: Single-layer coating and gradient construction.
[0042] A single-layer coating process is used to coat the slurry obtained in step S100 onto at least a portion of the surface of the current collector to form a wet film, and the wet film is then subjected to segmented drying.
[0043] It should be noted that the "single-layer coating process" refers to coating the negative electrode slurry onto the surface of the current collector in one go, and after drying and curing, forming a continuous active material layer without obvious interlayer interfaces.
[0044] In some embodiments of the present invention, the segmented drying process includes a first stage drying process and a second stage drying process, wherein the temperature of the first stage drying process is lower than the temperature of the second stage drying process, and the wind speed of the first stage drying process is lower than the wind speed of the second stage drying process.
[0045] By employing a segmented drying process, the solvent evaporation rate is controlled using a lower temperature and air velocity in the first stage, inducing the pore-forming agent to migrate away from the current collector along the solvent evaporation flow field. This creates a gradient distribution of pore-forming agent concentration that increases from the inside to the outside within the wet film. Subsequently, a higher temperature and air velocity in the second stage enable rapid coating curing, locking in the migration and distribution of the pore-forming agent. This process can construct a pore gradient structure in situ within a single layer of active material without multiple coatings. This not only simplifies the process and reduces production costs but also avoids the interfacial impedance problems associated with multilayer structures, ensuring the continuity and stability of the electrode's internal structure.
[0046] It should be noted that this application does not impose any particular restrictions on the specific heating method for the segmented drying process. In addition to hot air drying, infrared heating, microwave heating, and other methods can also be used. The key is to achieve slow solvent evaporation in the first stage and rapid coating curing in the second stage by adjusting the heating parameters. For example, when using infrared heating, the segmented drying effect can be achieved by controlling the heating power of the first stage to be lower than that of the second stage.
[0047] In some embodiments of the present invention, the temperature of the first drying process is 40°C-60°C, and the drying time is 5 min-20 min. Under these low temperature and low wind speed conditions, the evaporation rate of the solvent on the coating surface is slow, which promotes the continuous diffusion of the solvent inside the coating to the surface through capillary action, forming a solvent flow field pointing towards the coating surface. This flow field can carry the pore-forming agent (e.g., particle size of 50 nm-1 μm) away from the current collector, resulting in the enrichment of the pore-forming agent on the coating surface and the depletion of the underlying layer.
[0048] In some embodiments of the present invention, the temperature of the second drying process is 80℃-120℃, and the drying time is 10min-30min. Under these high temperature and high wind speed conditions, the solvent inside the coating evaporates rapidly, causing the coating to cure quickly and fixing the concentration distribution of the pore-forming agent.
[0049] It should be noted that this application does not impose any particular limitation on the method of driving the pore-forming agent to migrate directionally in the wet film. Besides the above-described embodiment that utilizes solvent evaporation to carry the pore-forming agent, those skilled in the art can also employ other driving methods to achieve the directional distribution of the pore-forming agent based on its physicochemical properties. For example, for pore-forming agents carrying charges or magnetism, their directional movement in the wet film can be driven by applying an electric or magnetic field; or, centrifugal force can be used to drive the migration of the pore-forming agent during the coating process. Any method that can create a pore-forming agent concentration gradient along the coating thickness direction, thereby forming a porosity gradient structure, falls within the technical scope of this application.
[0050] S300: Heat treatment.
[0051] The dried electrode is heat-treated at a temperature of 150℃-300℃ for 1h-6h. This step causes the pore-forming agent to decompose completely and volatilize and be removed, thereby forming a pore gradient structure corresponding to the concentration distribution of the pore-forming agent inside the active material layer. This results in the porosity of the electrode gradually increasing from the side closer to the current collector to the side farther away from the current collector along the thickness direction.
[0052] In other embodiments of this application, the pore gradient direction within the active material layer can also be reversed, i.e., the porosity gradually decreases from the side closer to the current collector to the side farther away, forming a structure with a dense surface layer and a loose inner layer. This structure is suitable for special applications requiring surface densification or internal liquid storage. Its preparation principle is similar to the embodiments described above, requiring only adjustment of the segmented drying process parameters. For example, a higher air velocity is used in the first stage of drying to promote rapid evaporation of the solvent on the coating surface, forming a dense layer, thereby inhibiting the migration of the pore-forming agent to the surface and retaining it within the coating. Such gradient direction adjustments based on the same migration mechanism fall within the technical scope of this application.
[0053] S400: Post-processing.
[0054] The heat-treated electrode sheets are rolled (compacted density controlled at 1.55-1.70 g / cm³) and slit to obtain the final negative electrode sheets.
[0055] This invention is based on a segmented drying process, achieving the directional migration of pore-forming agents under single-layer coating conditions, thereby forming a concentration gradient of pore-forming agents within a single coating layer, which is then transformed into a porosity gradient after heat treatment. Specifically, in the first stage of low-temperature, low-speed drying, the solvent evaporation rate on the coating surface is slow, while the solvent inside the coating continuously diffuses to the surface through capillary action, simultaneously carrying pore-forming agent microspheres with a particle size of 50nm-1μm to the surface, resulting in pore-forming agent enrichment on the surface and depletion at the bottom layer. In the second stage of high-temperature, high-speed drying, the coating rapidly solidifies, and the concentration distribution of the pore-forming agent is "frozen." Subsequent heat treatment causes the pore-forming agent to decompose and volatilize. The surface layer, due to its high pore-forming agent concentration, forms a high-porosity region, while the bottom layer, due to its low pore-forming agent concentration, forms a low-porosity region, with a transition region in between, ultimately resulting in a gradient structure where porosity increases from the inside to the outside along the thickness direction.
[0056] Furthermore, the preparation method provided in this application has good industrial applicability. Its improvement mainly lies in the optimization of existing coating and drying process parameters, without the need for new equipment or large-scale modification of production lines. Existing lithium-ion battery anode electrode production lines typically use coating machines with multiple drying zones. This application achieves the directional migration of the pore-forming agent by adjusting the temperature, wind speed, and residence time of each drying zone. For example, the temperature of the first drying zone can be set to 40℃-60℃, the wind speed controlled at a low level (e.g., fan frequency 20-30Hz), and the electrode residence time is 2-4 minutes; the temperature of the second drying zone can be set to 80℃-120℃, the wind speed controlled at a high level (e.g., fan frequency 50-60Hz), and the electrode residence time is 3-6 minutes. In addition, parameters such as slurry viscosity, solid content, and coating speed need to be matched with the drying process. For example, the solid content can be controlled at 40%-50%, and the coating speed can be controlled at 5-15 meters / minute. Those skilled in the art can make adaptive adjustments according to the actual equipment conditions.
[0057] Thirdly, this application provides a lithium-ion battery. According to an embodiment of this application, the lithium-ion battery includes the negative electrode sheet described in the first aspect, or a negative electrode sheet prepared by the method described in the second aspect. The lithium-ion battery possesses all the technical solutions of the negative electrode sheet, and therefore also possesses all the beneficial effects of the negative electrode sheet, which will not be elaborated upon here.
[0058] A lithium-ion battery comprises components such as a positive electrode, a negative electrode, a separator, and an electrolyte. Lithium-ion batteries can be manufactured using the following methods: Positive electrode production: The cathode material is at least one of lithium cobalt oxide (LiCoO2), lithium manganese oxide (LiMn2O4), lithium iron phosphate (LiFePO4), nickel-cobalt-manganese ternary materials (NCM), and nickel-cobalt-aluminum ternary materials (NCA). The conductive agent is at least one of conductive carbon black (Super P), Ketjen black (ECP), carbon nanotubes (CNT), conductive graphite (KS-6), and graphene. The binder is at least one of vinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE). The solvent is at least one of N-methylpyrrolidone (NMP), N,N-dimethylformamide (DMF), and dimethyl sulfoxide (DMSO).
[0059] Lithium-ion battery manufacturing process: The positive electrode, separator, and negative electrode (using the negative electrode of Examples 1-5 and Comparative Examples 1-2 respectively) prepared above are stacked in the order of "positive electrode / separator / negative electrode" and wound into a cell. The cell is then placed in an aluminum-plastic film shell, and the top and side seals are completed. The cells are baked at 80°C under vacuum for 24 hours to remove residual moisture from the electrodes and separator. Under inert gas protection, electrolyte is injected through the injection port and allowed to stand for 24 hours to allow the electrolyte to fully wet the electrodes and separator. The cells are charged at a constant current of 0.1C to 4.2V for formation, forming a stable SEI film on the surface of the negative electrode. The generated gas is removed during the formation process. The cells are then aged at 45°C for 72 hours to stabilize the battery performance. Finally, the cells are capacity-graded and tested at a current density of 0.5C / 0.5C. The cells are then screened according to capacity, and internal resistance, appearance, and safety performance are tested to obtain qualified lithium-ion batteries.
[0060] The separator is at least one of the following: polyethylene (PE) microporous membrane, polypropylene (PP) microporous membrane, PE / PP composite membrane, polyimide (PI) nanofiber membrane, polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP) separator, ceramic coated separator (Al2O3 or SiO2 coated on the PE / PP surface), and cellulose nonwoven fabric separator. The electrolyte comprises a lithium salt, a non-aqueous organic solvent, and a functional additive. The lithium salt is at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium bis(oxalato)borate (LiBOB), lithium difluorooxalato)borate (LiDFOB), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and lithium bis(fluorosulfonyl)imide (LiFSI). The non-aqueous organic solvent is at least one of ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), propylene carbonate (PC), ethyl acetate (EA), and γ-butyrolactone (GBL). The functional additive is at least one of vinylene carbonate (VC), fluoroethylene carbonate (FEC), 1,3-propanesulfonyl lactone (PS), vinyl sulfate (DTD), and succinic anionyl (SN).
[0061] The technical solution provided by the present invention will be described in detail below with reference to the embodiments.
[0062] Unless otherwise specified, the raw materials used in the examples and comparative examples are commercially available analytical grade materials.
[0063] Example 1 This embodiment provides a negative electrode sheet and its preparation method. 1. Slurry preparation: Graphite, silicon-carbon composite material (silicon content 10%), conductive agent (SP), binder (LA132), and pore-forming agent (PMMA microspheres, particle size 200nm) are mixed in a mass ratio of 60:30:5:5:5. NMP solvent is added, and the mixture is stirred evenly to obtain the negative electrode slurry. The pore-forming agent accounts for 5% of the mass of the slurry. 2. Coating: The slurry is coated onto the surface of the copper foil in a single layer, and the wet film thickness is controlled to be 150μm. 3. Segmented drying: First stage drying treatment: temperature 50℃, wind speed 2m / s, time 10min; Second stage drying treatment: temperature 100℃, wind speed 8m / s, time 20min. 4. Heat treatment: Place the dried electrode in a vacuum oven and heat treat it at 180℃ for 2 hours to decompose the pore-forming agent. 5. Rolling: Roll the electrode sheet to control the compaction density to 1.55 g / cm³ to obtain the negative electrode sheet. In this negative electrode sheet, the active material layer is a single-layer structure. Along the thickness direction, the porosity on the side closer to the current collector is 18%, and the porosity on the side farther away from the current collector is 42%. Example 2 The difference from Example 1 is that the temperature of the first drying process is 40°C and the time is 20 min; the temperature of the second drying process is 80°C and the time is 30 min; and the temperature of the heat treatment is 150°C and the time is 6 h.
[0064] The porosity of the resulting negative electrode sheet is 16% on the side near the current collector and 38% on the side away from the current collector.
[0065] Example 3 The difference from Example 1 is that the temperature of the first drying process is 60°C and the time is 5 min; the temperature of the second drying process is 120°C and the time is 10 min; and the temperature of the heat treatment is 300°C and the time is 1 h.
[0066] The porosity of the resulting negative electrode sheet is 20% on the side closer to the current collector and 45% on the side farther from the current collector.
[0067] Example 4 The difference from Example 1 is that the pore-forming agent accounts for 3% of the mass of the slurry, and the average particle size of the pore-forming agent is 1 μm.
[0068] The porosity of the resulting negative electrode sheet is 15% on the side closer to the current collector and 35% on the side farther from the current collector.
[0069] Example 5 The difference from Example 1 is that the pore-forming agent accounts for 15% of the mass of the slurry, and the average particle size of the pore-forming agent is 50 nm.
[0070] The porosity of the resulting negative electrode sheet is 25% on the side closer to the current collector and 50% on the side farther from the current collector.
[0071] Comparative Example 1 The difference from Example 1 is that segmented drying was not performed; instead, constant temperature drying (80°C, 30 min) was used. The resulting negative electrode sheet has a uniform porous structure with an overall porosity of approximately 25%.
[0072] Comparative Example 2 The difference from Example 1 is that a multi-layer coating process is used. The first layer of slurry does not contain a pore-forming agent, while the second layer contains a pore-forming agent. The two coatings are stacked after drying.
[0073] The resulting negative electrode sheet has a distinct interlayer interface, with a porosity of 10% on the side closer to the current collector and 45% on the side farther from the current collector.
[0074] Performance testing The negative electrode sheets of Examples 1-5 and Comparative Examples 1-2 were subjected to performance tests. The specific test methods are as follows: A lithium-ion test battery includes components such as a positive electrode, a negative electrode, a separator, and an electrolyte. The battery preparation method is as follows: Positive electrode production: The positive electrode material is a nickel-cobalt-manganese ternary material (NCM811), the binder is polyvinylidene fluoride (PVDF), and the solvent is N-methylpyrrolidone (NMP). The mass ratio of positive electrode material: conductive agent (Super P): binder (PVDF) = 90:5:5. After being mixed into a slurry, it is coated on both sides of the positive electrode current collector (aluminum foil) with a coating thickness of 100~150μm (single-sided). After drying and rolling, the positive electrode sheet is obtained.
[0075] Negative electrode production: The negative electrode sheets of Examples 1-5 and Comparative Examples 1-2 were used respectively.
[0076] Lithium-ion battery manufacturing process: The positive electrode, separator, and negative electrode are stacked in sequence and wound into a cell, which is then placed in a battery casing and sealed. After injecting electrolyte, the cell is allowed to stand, undergoing formation, aging, and capacity testing to obtain a lithium-ion battery. The separator is a polyethylene (PE) microporous membrane, and the electrolyte is a mixed solution of 1M LiPF6 dissolved in EC / EMC / DMC (volume ratio 1:1:1), with 2% vinylene carbonate (VC) added as an additive.
[0077] Electrode thickness expansion rate after 500 cycles: The electrode thickness before and after the cycle is measured with a micrometer, and the expansion rate is calculated using the formula: (thickness after cycle - thickness before cycle) / thickness before cycle × 100%.
[0078] Capacity retention after 500 cycles: Charge-discharge cycle test was performed at 0.5C / 0.5C current density, and the discharge capacity of the 1st and 500th cycles was recorded. Retention rate = discharge capacity of the 500th cycle / discharge capacity of the 1st cycle × 100%.
[0079] Interface impedance testing: Electrochemical impedance spectroscopy (EIS) was used for testing, with a frequency range of 100kHz to 10mHz and an amplitude of 5mV. The sum of the SEI film impedance and charge transfer impedance was obtained by equivalent circuit fitting.
[0080] The test results are shown in Table 1: Table 1 Performance Test Results
[0081] As shown in Table 1, compared with Comparative Examples 1-2, the negative electrode sheets of Examples 1-5 all exhibited lower electrode thickness expansion rates (15%-24% vs 28%-38%) and higher capacity retention rates (85.3%-93.5% vs 74.8%-82.1%) after 500 cycles. At the same time, the interface impedance was lower (10.9-15.6mΩ vs 16.8-19.3mΩ). This indicates that the pore gradient structure constructed by the present invention through single-layer coating combined with segmented drying can effectively buffer silicon volume expansion, maintain the integrity of the electrode structure, and reduce interface impedance, thus significantly improving the cycle stability and rate performance of the battery.
[0082] In Comparative Example 1, due to the lack of segmented drying, the pore-forming agent was uniformly distributed in the coating, forming a uniform pore structure after heat treatment. The high porosity of the inner layer (approximately 25%) resulted in insufficient bonding force between the active material and the current collector, failing to effectively guide the stress gradient distribution. The stress generated by silicon expansion formed local concentrations inside the electrode, accelerating electrode pulverization and conductive network breakage. Consequently, the capacity decay was severe in the later stages of cycling (retention rate of only 74.8%), and the electrode thickness expansion rate was as high as 38%.
[0083] Comparative Example 2, due to the use of a multilayer coating process, although a pore gradient can be formed, there is a clear physical interface between the layers. Under the stress of repeated expansion and contraction of silicon, the interlayer bonding force is weak and the interface impedance increases significantly (19.3mΩ), resulting in a decrease in rate performance and cycle stability (82.1% retention rate). Moreover, the multilayer coating process is lengthy and costly, which is not conducive to large-scale production.
[0084] In the description of this specification, the references to terms such as "one embodiment / mode," "some embodiments / modes," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment / mode or example is included in at least one embodiment / mode or example of the present invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment / mode or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments / modes or examples. Furthermore, without contradiction, those skilled in the art can combine and integrate the different embodiments / modes or examples described in this specification, as well as the features of different embodiments / modes or examples.
[0085] It should be noted that in this invention, relational terms such as "first" and "second" are used merely to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, technology, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, technology, article, or apparatus. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, technology, article, or apparatus that includes said element. In this invention, "a plurality of" means at least two, such as two, three, etc., unless otherwise expressly specified.
[0086] The above description is merely a specific embodiment of the present invention, enabling those skilled in the art to understand or implement the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the present invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features of the invention herein.
Claims
1. A negative electrode sheet, characterized in that, include: current collector; An active material layer is disposed on at least a portion of the surface of the current collector; wherein the active material layer is a single-layer structure, and the porosity of the active material layer increases in a gradient from the side closer to the current collector to the side farther away from the current collector, with the porosity on the side closer to the current collector being 15%-25% and the porosity on the side farther away from the current collector being 35%-50%.
2. The negative electrode sheet as described in claim 1, characterized in that, The active material layer includes graphite, silicon-carbon composite material, conductive agent, and binder.
3. A method for preparing a negative electrode sheet as described in claim 1 or 2, characterized in that, include: Prepare a slurry containing graphite, silicon carbide composite material, binder, solvent and pore-forming agent; The slurry is coated onto at least a portion of the surface of the current collector to form a wet film; The wet film is subjected to segmented drying. The dried electrode sheet is heat-treated to obtain the negative electrode sheet.
4. The preparation method according to claim 3, characterized in that, The pore-forming agent accounts for 3%-15% of the mass of the slurry.
5. The preparation method according to claim 3, characterized in that, The pore-forming agent has an average particle size of 50 nm to 1 μm; and / or, The pore-forming agent is a substance that can decompose in the range of 150-300 °C; and / or, The pore-forming agent includes at least one of polymethyl methacrylate microspheres, ammonium bicarbonate, polystyrene microspheres, polylactic acid microspheres, ammonium carbonate, and ammonium oxalate.
6. The preparation method according to claim 3, characterized in that, The segmented drying process includes a first stage drying process and a second stage drying process, wherein the temperature of the first stage drying process is lower than the temperature of the second stage drying process, and the wind speed of the first stage drying process is lower than the wind speed of the second stage drying process.
7. The preparation method according to claim 6, characterized in that, The temperature of the first drying process is 40℃-60℃, and the drying time is 5min-20min.
8. The preparation method according to claim 6, characterized in that, The temperature of the second drying process is 80℃-120℃, and the drying time is 10min-30min.
9. The preparation method according to claim 3, characterized in that, The heat treatment temperature is 150℃-300℃, and the time is 1h-6h.
10. A lithium-ion battery, characterized in that, Includes the negative electrode sheet as described in claim 1 or 2.